PENGARUH FORMULASI UKURAN PARTIKEL DAN SUHU PENGERINGAN TERHADAP AKTIVITAS ANTIOKSIDAN TEH HERBAL CELUP BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) - Muhammad Risan Hidayat; Alia Rahmi; lya agustina; Anhar Firdaus (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Bawang Dayak (Eleutherine palmifolia (L.) Merr.) is known as one of antioxidants sources because it has natural bioactive compounds such as phenol, flavonoids, tannins, glycosides, steroids, alkaloids which have good health benefits. Antioxidant can inhibit and prevent the damage caused by oxidation process of free radicals. Because of these benefits, bawang dayak is potential to be processed to a product such as herbal tea. The study aims to determine the effect of particle size formulation on drying temperature variation on antioxidant activity of bawang dayak herbal tea. The research method used is a randomized block design (RAK) of drying temperature consisting of one grouped factor that is the size formulation factor (F). The analysis performed on tea stock were water content, ash content, and presence of phytochemical compounds, while in brewed tea were acidity (pH), antioxidant activity (DPPH method), and sensory analysis (hedonic scale 1 – 5). The results indicated that the particle size formulation on drying temperature variation had an effect on the antioxidant activity. The best result was obtained from 100% coarse size formulation at 50oC drying temperature with the value of inhibition percentage (%) at 10 mg/ml of brewed tea is 77.38% and IC50 is 4.57 mg /ml brewed tea. The results of sensory analysis with hedonic scale for the treatment are for aroma (3.00; like slightly) and color (3.56; like), while taste can still be improved (2.32; dislike).